Impact of Educational Intervention on Knowledge and Attitude of Undergraduate Medical Students Regarding Pharmaceutical Promotion - Johora, Fatema; Rahman, Md Sayedur (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Promotional activities conducted by pharmaceutical industries are highly successful to alter physicians' prescribing habit. Undergraduate medical curriculum does not make students to deal with this unwarranted effect. Educational intervention might be a key to address this crucial issue. The aim of this study was to evaluate the impact of educational intervention on knowledge and attitude of medical students regarding pharmaceutical promotion. Materials and methods: This interventional research was conducted from February 2016 to February 2017. 4th year MBBS students of the four medical colleges of Dhaka city were the study population. A baseline assessment on knowledge and perception of the 4th year MBBS medical students' of the included medical colleges (Control and intervention) was conducted by a questionnaire survey. Number of respondents in control and intervention group was 156 and 243 respectively in pre test. Then, a package of educational intervention including interactive lecture and practical session was delivered to intervention group. After I month of intervention, post intervention data had been collected from undergraduate students to evaluate the effect of intervention on their knowledge and perception by using same questionnaire. Number of respondents in control and intervention group was 152 and 227 respectively in post test. Attitude of the undergraduate students of intervention group was evaluated by a structured questionnaire after one month of intervention. Total 227 students were participated in this survey. Results: Proportion of students regarding knowledge and perception about pharmaceutical promotion is significantly increased after intervention (p<0.001). Attitude of undergraduate students of intervention group on 10 different case scenarios related to pharmaceutical promotion have been changed after intervention and it were statistically significant in all 10 case scenarios. Conclusion: The conducted educational intervention was found effective at undergraduate level to modify knowledge and attitude about pharmaceutical promotion. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 8-13